Cinnamon Polyphenol Extract Exerts Neuroprotective Activity in Traumatic Brain Injury in Male Mice - Yulug, Burak; Kilic, Ertugrul; Altunay, Serdar; Ersavas, Cenk; Orhan, Cemal; Dalay, Arman; Şahin, Kazım (Bentham Science Publ, 2018)
Introduction: Cinnamon polyphenol extract is a traditional spice commonly used in different areas of the world for the treatment of different disease conditions which are associated with inflammation and oxidative stress. Despite many preclinical studies showing the anti-oxidative and anti-inflammatory effects of cinnamon, the underlying mechanisms in signaling pathways via which cinnamon protects the brain after brain trauma remained largely unknown. However, there is still no preclinical study delineating the possible molecular mechanism of neuroprotective effects cinnamon polyphenol extract in Traumatic Brain Injury (TBI). The primary aim of the current study was to test the hypothesis that cinnamon polyphenol extract administration would improve the histopathological outcomes and exert neuroprotective activity through its antioxidative and anti-inflammatory properties following TBI. Methods: To investigate the effects of cinnamon, we induced brain injury using a cold trauma model in male mice that were treated with cinnamon polyphenol extract (10 mg/kg) or vehicle via intraperitoneal administration just after TBI. Mice were divided into two groups: TBI+vehicle group and TBI+ cinnamon polyphenol extract group. Brain samples were collected 24 h later for analysis. Results: We have shown that cinnamon polyphenol extract effectively reduced infarct and edema formation which were associated with significant alterations in inflammatory and oxidative parameters, including nuclear factor-KB, interleukin 1-beta, interleukin 6, nuclear factor erythroid 2-related factor 2, glial fibrillary acidic protein, neural cell adhesion molecule, malondialdehyde, superoxide dismutase, catalase and glutathione peroxidase. Conclusion: Our results identify an important neuroprotective role of cinnamon polyphenol extract in TBI which is mediated by its capability to suppress the inflammation and oxidative injury. Further, specially designed experimental studies to understand the molecular cross-talk between signaling pathways would provide valuable evidence for the therapeutic role of cinnamon in TBI and other TBI related conditions.
Keywords: Cinnamon; Traumatic brain injury; Glial fibrillary acidic protein; Interleukin 1-beta; Interleukin 6; Neural cell adhesion molecule; Nuclear factor-kappa B; Nuclear factor erythroid 2-related factor 2; Malondialdehyde; Superoxide dismutase; Catalase; Glutathione peroxidase